Teaching Scheme Research on Issues of Marine Environment Education: Taking the Interdisciplinary Integration of Biology, Chinese, and Information into Marine Biology as an Example - Pai-Lu Wu, Chia-Mei Lu1 , Su-Mei Wu , Mei-Shih Tsa Ming-Cheng Wang, (International Journal of Scientific Research and Management (IJSRM), 2017)
In order to meet the spirit of interdisciplinary teaching, this study combined the existing teaching materials with students' life experience using the existing resources in the community to train their ability to achieve mastery in any area of their life. Focusing on the ecological teaching in the Museum of Marine Biology and Aquarium, teachers in the subjects of biology, Chinese, and information discussed the teaching direction and designed a series of teaching programs in a comprehensive way. The course ran for one year with a total of 72 classes and two classes a week. The teachers in the three subjects carried out collaborative teaching according to the contents they had prepared together. The objects of this study were 33 high school students who participated in the biology curriculum. It was hoped that they would be provided with a more comprehensive and integrated education and their interest in learning would be cultivated through integrating interdisciplinary teaching into marine education. The research conclusions are: 1) through the systematic and cross-curricular courses prepared together and curriculum activities, students were able to learn more fully and effectively integrate the content of those subjects; and 2) through the strategy of outdoor teaching at Ocean Fantasy Museum, the interest and learning attitude of high school students were effectively promoted and students' knowledge on marine organisms was enhanced. Therefore, the design and implementation of a cross-curriculum teaching plan in this course can contribute to the expansion of marine education.